A mídia digital e a relação com a criança da educação infantil: percepções dos professores sobre interatividade e processos comunicacionais - Novak, Emilene da Conceição (2014)
This study analyzes the perception of teachers about the communicational relation accomplished by the use of digital medias with four and five-year-old children who attend public schools in the last stage of pre-school. The problem that founds this research is to ascertain the manner by which teachers perceive the contributions of the communication processes and of the digital medias to their students‟ learning process accomplished through interaction. This research aims at acknowledging the interferences that the information society exerts in the communication processes, perceiving, through the teacher, how interactivity with the digital medias in pre-school occurs, and in addition, observing the application by the teachers when using digital medias, particularly the computer. It is also our intent to analyze the interface Communication-Education and the main practices of educommunication, in view of the digital medias. The relation between education and communication is evident throughout this paper, which takes into perspective cultural and technological aspects of early childhood education. The methodology applied will initiate with a descriptive exploratory study, using qualitative analyses of the interviews made with pre-school teachers of a public school in the countryside of Paraná, as well as literature on the subject at hand, digital media and common knowledge about technology which influence all the pedagogic work of the stage prior to elementary school. The results of the research lead to the deduction that teachers do not have a clear perception of the full extent of what interactivity and communication processes truly convey. For such reason, it has been concluded that, a lasting practice should entail a full integration of the Digital Information and Communication Technologies with the school day-in and day-out pedagogic practices, in addition to a continuing education programme.